Two new ovoviviparous species of the family Selachinematidae and Sphaerolaimidae (Nematoda, Chromadorida & Monhysterida) from the northern South China Sea - Fu, Sujing; Boucher, Guy; Cai, Lizhe (Zootaxa, 2017)
Two new ovoviviparous nematode species are described from South China Sea. Bendiella vivipara n. sp. belongs to the family Selachinematidae and is characterized by a cuticle with lateral differentiation of 2–4 longitudinal rows of dots, and the presence of 3 papillose precloacal supplements. Parasphaerolaimus jintiani n. sp. is characterized by a cuticle with lateral longitudinal unstriated band extending from about the middle of the pharynx to the anterior two-thirds of the tail and a vulva situated far posteriorly. The importance of ovoviviparity in free living marine nematodes is discussed.